Conscious sedation - Wiener-Kronish, Jeanine P. (Hanley & Belfus, 2001)
This book is a comprehensive review of conscious sedation in both the inpatient and outpatient settings. The authors review guidelines and requirements for office-based conscious sedation, including medicolegal issues.